The Impact of Breast Pump Usage of Breastfeeding Mother: Scoping Review - Sakinah Yusro Pohan; Sri Ratna Ningsih; Andari Wuri Astuti (International Journal of Health Science and Technology, 2021)
Background: WHO recommended that mother breastfeeds exclusively for the fisrt six months. However, a lot of mothers do not realize it. Generally, the anxiety on milk production, the family and occupation commitment, waking up at night and perceiving uncomfortable breastfeeding in public place become the objectives of this study that is for reviewing evidence related the impact of breast pum usage on breastfeeding mother. Method: According to ArskeyO’Malley include (1)Identifying scoping review questions are conducting review focus with PICO framework (2)Identifying relevant article (3)Selecting article (4)Data Charting and (5)Arranging, summing up and reporting findings. Results: The theme of scoping review is the impact of breastfeeding success, the negative outcome of breast pump, and the factors which influence decision for mother’s milk pumping as well supporting for breast pump. Conclusion: the impact of breast pump usage affects breastfeeding duration and mother’s milk production as well as painful breast.